Keanekaragaman Mikoriza Arbuskula Pada Tanaman Nanas (Ananas comosus L) Yang di Tanam Pada Tanah Gambut Sungai Raya Kabupaten Kubu Raya - Ikrimah, Ikrimah; Ir.Ismahan Umran, M.Si, Ir.Ismahan Umran, M.Si; Ir. H.Riduansyah,MP, Ir. H.Riduansyah,MP (Jurnal Sains Mahasiswa Pertanian, 2016)
Mycorrhizal Arbuscular (MA) is a potential of natural resources found in nature and can be found almost all ecosystems. Mycorrhiza is one of association between roots and fungi. Influenced by environmental factors such as soil temperature, soil moisture, soil pH, organic material, light intensity and the host plant. This study aims to determine species diversity of arbuscular mycorrhizal (AM) in pineapple plant (Ananas comosus L) grown on peat Soil at Sungai Raya Subdistrict Kubu Raya. Observation variables observed species diversity, evenness abundance of spesies, pH, temperature, C-Organik, rainfall. Results obtained insulation 660 spores/100 g soil and 12 spore types Nanas location Sungai Asam with diversity index of 1.63, 922 spores/100 g soil in Pineapple Village location Rejosari 922 spores / 100 g soil and 10 types of spores in a diversity index of 1,66 Â and 1028 spores / 100 g soil and 16 types of spores in the secondary forest with a diversity index of 1,9. The results showed that the Mycorrhizal Fungi on the third location of the observations show the diversity criteria